OPTIMAL PLACEMENT OF HYSTERETIC OR VISCOUS DAMPER BASED ON THE INCREMENTAL INVERSE PROBLEM - Sanchez, Wilson Emilio David; Avila, Suzana Moreira; Brito, Jose Luis Vital de (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
Structural control system aims to improve the protection of buildings and civil structures, occupants and contents from the destructive forces of nature due to earthquakes, wind and waves. Control techniques can be classified according to how the system manipulates, absorbs and dissipates the imposed energy. Passive damping system absorbs or consumes a portion of the input energy, reducing energy dissipation on primary structural members and does not require an external power source. In this work the efficiency of four Matlab programmed routines in terms of time or computational cost and flexibility according to the type of damper will be assessed. Two techniques were evaluated: (a) An analytical procedure known as incremental inverse problem for redesign of structural system with a hysteretic damping system for target transfer functions and (b) to apply an efficient and systematic procedure for to find the optimal damper placement to minimize the sum of amplitudes of the transfer functions evaluated at the undamped fundamental natural frequency of a structural system subject to a constraint on the sum of the damping coefficients of added dampers.